Effect of laser fluence on structural and optical properties of CuxS films grown by pulsed laser deposition at different wavelengths - P E Rodríguez-Hernández; J G Quiñones-Galván; M Meléndez-Lira; J Santos-Cruz; G Contreras-Puente; F de Moure-Flores (Materials Research Express, 2020)
Cu _x S thin films were grown onto soda-lime glass substrates by pulsed laser deposition at two different wavelengths: 1064 and 532 nm. X-ray diffraction, Raman and UV–vis spectroscopies were used to characterize the Cu _x S films. Results are presented as a function of laser fluence. XRD patterns indicate that covellite and chalcocite phases were obtained. Raman spectra showed that chalcocite is the predominant phase in the crystalline samples. Optical band gap values are between 2.29 and 2.74 eV for ablation with 1064 nm wavelength; meanwhile, for 532 nm band gap values varied from 2.24 to 2.66 eV; which are in the range of expected values for Cu _x S films. At 1064 nm and 4.4 J cm ^−2 sample presented the highest optical absorbance in the visible range, which corresponds to the highest thickness. These are the best growth parameters for Cu _x S films in order to be used as absorber films for solar cells applications.